On Certain Class of Non-Bazilevič Functions of Order α+iβ Defined by a Differential Subordination. (17th July 2014) - Alamoush, A. G.; Darus, M.
Abstract : We introduce a new subclassN n ( λ, α, β, A, B ) of Non-Bazilevič functions of orderα + i β . Some subordination relations and inequality properties are discussed. The results obtained generalize the related work of some authors. In addition, some other new results are also obtained.